Complex virus diseases of sweet potato - Rossel, H.W.; Thottappilly, G. (1988)
Both components of the virus complex that causes the sweet potato virus disease (SPVD) in Nigeria can individually be transmitted by their respective vectors from diseased sweet potato to healthy sweet potato and to the test plant, Ipomoea setosa. But in isolation, neither the aphid nor the whitefly-transmitted component, both latent in sweet potato, can be thus transmitted.